Government must proceed with landmark anti-obesity regulations in England. (30th September 2022) - Muir, Sarah; Dhuria, Preeti; Vogel, Christina
Abstract : Anti-obesity measures can change the current trajectory of rising levels of diet related illnesses and deaths, say Christina Vogel and colleagues